THE IMPORTANCE OF IMPLEMENTING THE ISM CODE IN THE MACHINE ROOM AT KM. ADITHYA - Sibali, Alwi; Rachman, Abdul Nasir (Indonesian Journal Of Maritim Review, 2023)
In accordance with the awareness of the importance of human factors and the need to improve ship operational management in preventing ship, human, cargo and property accidents and preventing pollution of the marine environment, IMO issued a regulation on ship safety management & marine environment protection known as the International Safety Management (ISM Code) which was also consolidated in the SOLAS convention. This research was carried out on the KM ship. ADITHYA on the Pare-pare – Samarinda cruise. PT. Afta Trans Mandiri. Based on the results of this study, it can be concluded that several things about Safety Management are as follows introduction of Safety Management is very important for the company or for ships because the process of understanding Safety Management for companies will be able to compete for the market